Questioning heteronormative higher education spaces: experiences of lesbian women at a South African university - Naidu, M.; Mutumbara, V. (South African Journal of Higher Education, 2017)
This paper narrows the gaze on sexual orientation and focuses on a group of university-going women who self-identify as lesbian. The paper works from the understanding that there is an intersectional prism through which women’s experiences need to be understood. Thus, working within an intersectional paradigm and narrative analysis, the paper attempts to situate the experiences and shared stories of a core sample community of a small group of university women against a human rights discourse and what is understood by the women as their entitlement to full sexual citizenship within the institutional spaces of the university. Findings reveal that the women feel that the imperatives of university transformation hold little meaning in terms of their personal sexual orientation. Findings also show that in the perceived absence of institutional support, the women draw on nodal ties and social capital embedded in student social groups where kinship and acceptance is offered.